2011
DOI: 10.1111/j.1468-1331.2011.03414.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is associated with migraine and migraine‐related metabolic risk in females

Abstract: We show here that increased oxidative stress is associated with migraine and contributes to migraine-related metabolic risk like nitrosative stress, an atherogenic lipid profile and hyperinsulinemia. Our data suggest that oxidative stress may represent a key event in the pathophysiology of migraine and a suitable therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
97
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(108 citation statements)
references
References 44 publications
6
97
2
Order By: Relevance
“…Population-based studies have verified the associations of several conditions, such as stroke (6), depression (7), anxiety disorders (8), epilepsy (9) and sensorineural hearing loss (10), with migraine. Intriguingly, in a cross-sectional population-based twin study, Bernecker et al (11) found that migraine was comorbid with urinary calculi. Clinically, concern about the association between migraine and urinary calculi has increased, as the latter have been reported as a complication of topiramate, a frequently prescribed anti-epileptic and migraine-preventive agent (12).…”
Section: Introductionmentioning
confidence: 95%
“…Population-based studies have verified the associations of several conditions, such as stroke (6), depression (7), anxiety disorders (8), epilepsy (9) and sensorineural hearing loss (10), with migraine. Intriguingly, in a cross-sectional population-based twin study, Bernecker et al (11) found that migraine was comorbid with urinary calculi. Clinically, concern about the association between migraine and urinary calculi has increased, as the latter have been reported as a complication of topiramate, a frequently prescribed anti-epileptic and migraine-preventive agent (12).…”
Section: Introductionmentioning
confidence: 95%
“…Malondialdehyde (MDA) levels and erythrocyte superoxide dismutase (SOD) activity were, indeed, significantly higher in migraineurs than in controls, as shown by Tuncel et al The SOD activity was significantly higher in the MA subgroup as compared to MO [22]. The levels of 4-hydroxy-2-nonenal (HNE), increased in female patients compared to controls (OR for migraine of 4.55), were significantly correlated with the nitric oxide pathway, insulin- and lipid-metabolism [23]. Furthermore, Gupta et al assessed the oxidative stress in migraineurs and TTH subjects by collecting a venous blood sample from the antecubital vein at least 3 days after the last headache attack.…”
Section: Reviewmentioning
confidence: 98%
“…1 A growing body of evidence indicates that increased oxidative stress (OS) is a key event in migraine pathophysiology. 4 Moreover, OS has also been hypothesized as a suitable therapeutic target in migraine. 4 Moreover, OS has also been hypothesized as a suitable therapeutic target in migraine.…”
mentioning
confidence: 99%
“…2 OS may contribute to damage in periaqueductal gray and in deep brain nuclei with repeated migraine attacks 3 and to migraine-related metabolic alterations. 4 Specific changes in genes expression in the brain that are involved in OS responses, such as major prion protein (PrP), have been documented in animals during cortical spreading depression (CSD), 5 the putative neurophysiological mechanism of migraine aura that might also occur in clinically silent brain areas in migraine without aura. 4 Specific changes in genes expression in the brain that are involved in OS responses, such as major prion protein (PrP), have been documented in animals during cortical spreading depression (CSD), 5 the putative neurophysiological mechanism of migraine aura that might also occur in clinically silent brain areas in migraine without aura.…”
mentioning
confidence: 99%